THREE-ELECTRODE AIR SWITCHBOARD WITH THE GRAPHITE ELECTRODES OF KATG-50 ON VOLTAGE TO ±50 KV AND IMPULSE CURRENT BY AMPLITUDE TO ±220 KA - M. I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2015)
Purpose. Development and creation of the simplified construction of a high-voltage heavy-current air three-electrode switchboard with graphite electrodes, intended for operation in composition the powerful generator of large impulsive current of artificial of linear lightning. Methodology. Electrophysics bases of technique of high-voltage and scientific and technical bases of planning of devices of high-voltage impulsive technique. Results. Developed and made a new construction of a high-voltage heavy-current air three-electrode switchboard with the graphite electrodes of KATG-50 on nominal voltage ±50 kV. This construction of switchboard KATG-50 has been passed experimental approbation in composition the heavy-current bit chain of powerful high-voltage generator of the аperiodic impulses of current of artificial linear lightning rationed on operating foreign standards with amplitude of Im=±(200±20) кА at their duration τP=(350±35) μs at level 0,5∙Im. Originality. First in domestic practice of development and creation of high-voltage heavy-current switchboards for the generators of large impulse currents of artificial lightning the ground of necessity of the use for their basic and managing electrodes of electrical engineering graphite is carried out. Practical value. The developed and made high-voltage heavy-current switchboard of cascade-tray KATG-50 from application in its composition of graphite electrodes possesses an enhanceable working resource and enhanceable stability of wearing-out at the use of similar switchboard in the bit chain of powerful pulsed current of the imitated linear lightning.